An academic profile of first-year engineering students - Vasconcelos, Rosa (2006)
Social and cultural diversification increases the student’s heterogeneity in higher education in Portugal. This article will analyse some variables that characterise first-year university students of engineering courses at the University of Minho. Aspects like learning habits and Approach, entrance grade, as well as vocational choice will be analysed. Some differences considering gender have been found, namely better daily study activities organization and time management in female students.